2010
DOI: 10.2522/ptj.20090077
|View full text |Cite
|
Sign up to set email alerts
|

Novice and Experienced Physical Therapist Clinicians: A Comparison of How Reflection Is Used to Inform the Clinical Decision-Making Process

Abstract: The results of this study may be used by educators and employers to develop and structure learning experiences and mentoring opportunities to facilitate clinical decision-making abilities and the development of the skills necessary for reflection in students and novice practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 29 publications
4
81
1
2
Order By: Relevance
“…16 It has also been suggested that physiotherapists' choice of treatment techniques is usually based on the initial academic and clinical training they received and their prior experience with patients, not on the literature. 20,27 However, our results are not directly comparable to those of Wainwright and colleagues (2011), 19 as we did not use the same classification system for clinical decisionmaking factors.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…16 It has also been suggested that physiotherapists' choice of treatment techniques is usually based on the initial academic and clinical training they received and their prior experience with patients, not on the literature. 20,27 However, our results are not directly comparable to those of Wainwright and colleagues (2011), 19 as we did not use the same classification system for clinical decisionmaking factors.…”
Section: Discussioncontrasting
confidence: 56%
“…[16][17][18][19][20][21][22] Physiotherapists with more experience have been shown to have advanced cognitive strategies and problem solving skills supporting their clinical rationale for treatment application. 16 Furthermore, experienced physiotherapists are more readily able to adapt to varying clinical circumstances and develop their own criteria for standards of practice and treatment selection.…”
mentioning
confidence: 99%
“…In a study comparing clinical decision making of novice and experienced clinicians, researchers found that each engaged in similar but different types of reflection during the clinical decision-making process. 28 Relevant findings from this research include the importance of novices having time to reflect on clinical decision making, having the opportunity to discuss reflections with a mentor, and gaining insight into how seasoned clinicians use reflection. The authors suggest that the development of reflection and metacognition skills are essential in assisting the students in the transition from classroom knowledge to real-world application and subsequent growth as a practitioner in the field.…”
Section: Positive Experiencementioning
confidence: 99%
“…The type of reflection that is commonly used as an exercise in decision making processes for students in the various healthcare professions is reflection on action (Conte, 2015;Wainwright, Shepard, Harman & Stephens, 2010).…”
Section: Reflection and Critical Thinkingmentioning
confidence: 99%